SpyandGo purification of SpyTag-proteins using pseudo-SpyCatcher to access an oligomerization toolbox - Khairil Anuar, INA; Banerjee, A; Keeble, AH; Carella, A; Nikov, GI; Howarth, M (Nature, 2019)
Peptide tags are a key resource, introducing minimal change while enabling a consistent process to purify diverse proteins. However, peptide tags often provide minimal benefit post-purification. We previously designed SpyTag, forming an irreversible bond with its protein partner SpyCatcher. SpyTag provides an easy route to anchor, bridge or multimerize proteins. Here we establish SpyandGo, enabling protein purification using SpyTag. Through rational engineering we generated SpyDock, which captures SpyTag-fusions and allows efficient elution. SpyandGo enabled sensitive purification of SpyTag-fusions from Escherichia coli, giving superior purity than His-tag/nickel-nitrilotriacetic acid. SpyandGo allowed purification of mammalian-expressed, N-terminal, C-terminal or internal SpyTag. As an oligomerization toolbox, we established a panel of SpyCatcher-linked coiled coils, so SpyTag-fusions can be dimerized, trimerized, tetramerized, pentamerized, hexamerized or heptamerized. Assembling oligomers for Death Receptor 5 stimulation, we probed multivalency effects on cancer cell death. SpyandGoo, combined with simple oligomerization, should have broad application for exploring multivalency in signaling.